Seroprevalence of Toxoplasma gondii Infection Among Β-Thalassemia Major Pediatric Population: Implications for Transfusion Transmissible Toxoplasmosis. Issue 3 (March 2019) - El-Tantawy, Nora; Darwish, Ahmad; Eissa, Eman
Abstract : Background: Children with β-thalassemia major who regularly receive blood transfusion are at risk of developing transfusion-transmitted infection. Toxoplasmosis is a common and a serious parasitic disease with high prevalence and could be transmitted through blood transfusion from healthy asymptomatic donors. However, screening Toxoplasma gondii before blood donation has not been considered. The objective of this study was to determine the prevalence of T. gondii antibodies among thalassemia children undergoing blood transfusion. Methods: In a case–control study, serum samples from 211 thalassemia children and 100 control children were investigated for Toxoplasma IgM and IgG using the enzyme-linked immunosorbent assay. Positive serum samples for IgG antibodies to T. gondii were further subjected to IgG avidity enzyme-linked immunosorbent assay. Results: The seroprevalence of Toxoplasma infection among thalassemia children was 23.2% and 53.6% for IgM and IgG anti- Toxoplasma antibodies, respectively. Whereas in the control group, the prevalence was 5% and 18% for IgM and IgG anti- Toxoplasma antibodies, respectively. There is a significant statistical difference between thalassemia and control groups regarding the prevalence of toxoplasmosis. From these positive IgG samples, 65.5% have low avidity indicating recent infection while 38.73% have high avidity indicating past infection. Conclusion: Due to the high serologic infection rate of toxoplasmosis among thalassemia pediatric population in this study with no existing effective therapies and no available T. gondii vaccine, appropriate strategies are critical for reducing the risk of that infection. Screening of blood for T. gondii antibodies should be considered before transmission to those children especially in countries with a high prevalence of toxoplasmosis.